Vilazodone in patients with generalized anxiety disorder. (November 2015) - Gommoll, Carl; Forero, Giovanna; Mathews, Maju; Nunez, Rene; Tang, Xiongwen; Durgam, Suresh; Sambunaris, Angelo
<x xml:space="preserve">Abstract</x> Vilazodone is a selective serotonin reuptake inhibitor and a 5-HT1A receptor partial agonist that is approved for treatment of major depressive disorder in adults in the USA and Mexico. The efficacy, safety, and tolerability of vilazodone for generalized anxiety disorder (GAD) were investigated in a clinical trial (NCT01766401 ClinicalTrials.gov). Participants (18–70 years, inclusive) who met Diagnostic and Statistical Manual of Mental Disorders, 4th ed., text revision, criteria for GAD were randomized (1 : 1) to placebo or flexible-dose vilazodone (20–40 mg/day) for 8 weeks of double-blind treatment. Primary and secondary efficacy parameters were changes from baseline to week 8 in Hamilton Rating Scale for Anxiety and Sheehan Disability Scale total scores, respectively. Analysis was based on a mixed-effects model for repeated measures approach on the intent-to-treat population. The intent-to-treat population comprised 395 patients (placebo=197, vilazodone=198); 77% completed the study. The least squares mean difference in change from baseline to week 8 in the Hamilton Rating Scale for Anxiety total score was statistically significant for vilazodone versus placebo [−1.50 (−2.96, −0.04), P=0.0438]. The mean change from baseline to week 8 in the Sheehan Disability Scale total score for vilazodone versus placebo was not statistically significant. Adverse events were reported in 60% of placebo-treated and 83% of vilazodone-treated patients. This was a positive clinical trial of 20–40 mg/day vilazodone versus placebo in the treatment of GAD.